PENGARUH PROFITABILIAS, SOLVABILITAS, UKURAN PERUSAHAAN DAN SENSIVITAS INDUSTRI TERHADAP PENGUNGKAPAN LAPORAN KEBERLANJUTAN: THE EFFECT OF PROFITABILITY, LEVERAGE, COMPANY SIZE AND INDUSTRY SENSITIVITY ON THE DISCLOSURE OF SUSTAINABILITY REPORT - Anggara, Bayu; Surya, Raja Adri Satriawan; Azhar.L, Al (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
A sustainability report is a report that provides information regarding a company's impact on environmental, social and economic aspects. It is hoped that this sustainability disclosure report will attract the attention of companies in global business and increase public trust and the willingness of stakeholders to invest capital in the company. because there are still many companies that have gone public but have not yet disclosed their sustainability reports. This research aims to analyze the influence of profitability, ileverage, company size, and industry sensitivity on SustainabilityiReport disclosure. In this research, there were 213 manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2019–2021. The sampling method used was purposive sampling. The number of samples in this research was 105 manufacturing companies in 2019–2021. The analysis tool uses multiple linear regression tests. The research results show that leverage and industry sensitivity have no effect on Sustainability Report disclosure. Meanwhile, profitability and company size influence the disclosure of the Sustainability Report. In sustainability reports, disclosure has implications not only for fulfilling regulatory obligations, but can also have a significant impact on a company's reputation and relationships with stakeholders.